Radial Menu for Virtual Reality Based on Wrist Rotation - Di Domenico, Gabriel; Berwaldt, Natan; D'Avila, Mauren W.; Pozzer, Cesar (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
Rapid interaction with menus plays a crucial role in fast-paced real-time applications such as games and simulations, confronted with menus that contain a large number of options, especially when considering applications in virtual reality (VR). The conventional selection methods, such as raycasting, commonly used in these scenarios, tend to be cumbersome, imprecise and require unnecessary movements. To overcome these limitations, this paper explores different techniques that use the wrist rotation to interact with radial menus in an efficient and intuitive way. An experimental study was conducted involving multiple users to compare the effectiveness of the different solutions, demonstrating their ability to deliver seamless and efficient interactions within the virtual reality environment.